2016
DOI: 10.18632/oncotarget.13107
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 suppresses interleukin-10 via inhibiting A20 in peripheral B cells of patients with food allergy

Abstract: The regulatory B cells (Breg) are important in the body immunity. The differentiation process of Breg is not fully understood yet. Ubiquitin A20 has immune regulatory functions. This study aims to investigate the role of A20 in the regulation of interleukin (IL)-10 in B cells. In this study, B cells were isolated from the peripheral blood samples of healthy subjects and patients with food allergy (FA). The B cells were analyzed by flow cytometry, real time RT-PCR, Western blotting and chromatin immunoprecipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…The role of A20 in inflammatory conditions has been well documented. An important anti‐inflammatory role for this ubiquitin has been reported in arthritis, auto‐immune diseases, cardiovascular diseases, cystic fibrosis, chronic obstructive pulmonary disease (COPD), allergies and asthma . In addition, the modulation of the expression of A20 has been demonstrated to be an important mechanism of action of certain drugs including methotrexate, quercetin and the combination of long‐acting β 2 ‐adrenoceptor agonistsand glucocorticoids .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of A20 in inflammatory conditions has been well documented. An important anti‐inflammatory role for this ubiquitin has been reported in arthritis, auto‐immune diseases, cardiovascular diseases, cystic fibrosis, chronic obstructive pulmonary disease (COPD), allergies and asthma . In addition, the modulation of the expression of A20 has been demonstrated to be an important mechanism of action of certain drugs including methotrexate, quercetin and the combination of long‐acting β 2 ‐adrenoceptor agonistsand glucocorticoids .…”
Section: Discussionmentioning
confidence: 99%
“…An important anti-inflammatory role for this ubiquitin has been reported in arthritis, auto-immune diseases, cardiovascular diseases, cystic fibrosis, chronic obstructive pulmonary disease (COPD), allergies and asthma. 20,[27][28][29][30][31][32][33] In addition, the modulation of the expression of A20 has been demonstrated to be an important mechanism of action of certain drugs including methotrexate, quercetin and the combination of long-acting β 2 -adrenoceptor agonistsand glucocorticoids. [34][35][36][37] Moreover, it has recently been reported that there is a positive association between a polymorphism in the A20 gene and susceptibility to human asthma in the population investigated in the GABRIELA study, a study that focuses on the effects of farm environments on asthma and allergy in children from central Europe.…”
Section: This Disparity Between the Pharmacokinetic And Pharmacodynamicmentioning
confidence: 99%
“…RNA was reverse-transcribed into cDNA by a Multiscribe™ Reverse Transcriptase kit (Applied Biosystems, Foster City, CA, USA). Real time PCR (qPCR) was performed following the primers and protocol provided by Li et al [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are 18HDACs in mammals that are classified into four classes. Class III HDACs (known as sirtuins) are NAD + -dependent, while class I, II and IV HDACs are all zinc-dependent.Class I HDACs, which consists of HDAC1, 2, 3, and 8, are homologous to yeast Rpd3.Class II HDACs are homologous to yeast Hda1 and can be further divided into two subclasses: IIa (HDAC4,5,7,9) and IIb (HDAC6, 10) 1,3 . Class IV HDAC, which is not highly homologous to either Rpd3 or Hda1 yeast enzymes, is comprised solely of HDAC11 4,5 .HDAC11 is normally found in brain, testis, and immune cells such as antigenpresenting cells (APCs) 5,6 .…”
mentioning
confidence: 99%
“…Class II HDACs are homologous to yeast Hda1 and can be further divided into two subclasses: IIa (HDAC4,5,7,9) and IIb (HDAC6, 10) 1,3 . Class IV HDAC, which is not highly homologous to either Rpd3 or Hda1 yeast enzymes, is comprised solely of HDAC11 4,5 .…”
mentioning
confidence: 99%